Tuning acoustic and mechanical properties of materials for ultrasound phantoms and smart substrates for cell cultures. (February 2017) - Cafarelli, A.; Verbeni, A.; Poliziani, A.; Dario, P.; Menciassi, A.; Ricotti, L.
Graphical abstract: Abstract: Materials with tailored acoustic properties are of great interest for both the development of tissue-mimicking phantoms for ultrasound tests and smart scaffolds for ultrasound mediated tissue engineering and regenerative medicine. In this study, we assessed the acoustic properties (speed of sound, acoustic impedance and attenuation coefficient) of three different materials (agarose, polyacrylamide and polydimethylsiloxane) at different concentrations or cross-linking levels and doped with different concentrations of barium titanate ceramic nanoparticles. The selected materials, besides different mechanical features (stiffness from few kPa to 1.6 MPa), showed a wide range of acoustic properties (speed of sound from 1022 to 1555 m/s, acoustic impedance from 1.02 to 1.67 MRayl and attenuation coefficient from 0.2 to 36.5 dB/cm), corresponding to ranges in which natural soft tissues can fall. We demonstrated that this knowledge can be used to build tissue-mimicking phantoms for ultrasound-based medical procedures and that the mentioned measurements enable to stimulate cells with a highly controlled ultrasound dose, taking into account the attenuation due to the cell-supporting scaffold. Finally, we were able to correlate for the first time the bioeffect on human fibroblasts, triggered by piezoelectric barium titanate nanoparticles activated by low-intensity pulsed ultrasound, with a precise ultrasound dose delivered. These results may open new avenues for the development of both tissue-mimicking materials for ultrasound phantoms and smart triggerable scaffolds for tissue engineering and regenerative medicine. Statement of Significance: This study reports for the first time the results of a systematic acoustic characterization of agarose, polyacrylamide and polydimethylsiloxane at different concentrations and cross-linking extents and doped with different concentrations of barium titanate nanoparticles. These results can be used to build tissue-mimicking phantoms, useful for many ultrasound-based medical procedures, and to fabricate smart materials for stimulating cells with a highly controlled ultrasound dose. Thanks to this knowledge, we correlated for the first time a bioeffect (the proliferation increase) on human fibroblasts, triggered by piezoelectric nanoparticles, with a precise US dose delivered. These results may open new avenues for the development of both tissue-mimicking phantoms and smart triggerable scaffolds for tissue engineering and regenerative medicine.